Best Answer

Sure. It requires only the most basic algebraic manipulation of equalities.

x2 + 6 = -4x2 + 2

Add 4x2 to each side:

5x2 + 6 = 2

Subtract 2 from each side:

5x2 + 4 = 0

ax2 + bx + c = 0

a = 5

b = 0

c = 4

Q: Can you put the equation x2 plus six equals negative four x2 plus two in the form ax2 plus bx plus c equal 0?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Multiply the equation by negetive 1. So, -2x+y=1 becomes 2x-y=-1.

The equation ax2 + bx + c = 0, where a != 0 is called quadratic.

I don't see an equation. An equation must have an equal sign. For a question in answers.com, you'll have to write the word "equals", since symbols get lost.

A quadratic equation.

Ax+By=C A- Cannot be negative Equation- Cannot have decimals or fractions in it

Related questions

Multiply the equation by negetive 1. So, -2x+y=1 becomes 2x-y=-1.

The equation ax2 + bx + c = 0, where a != 0 is called quadratic.

I don't see an equation. An equation must have an equal sign. For a question in answers.com, you'll have to write the word "equals", since symbols get lost.

A quadratic equation.

2

Ax+By=C A- Cannot be negative Equation- Cannot have decimals or fractions in it

That will depend on what negative something equals which has not been given.

A mathematical sequence whose verb is equal is the definition for an equation. An equation is given in the form A is equal to B. An equation can contain numbers and variables.

Solving the equation for "y" gives you the slope-intercept form.

9

When two expressions are equal they can form an equation.

It is the general form of a quadratic equation.